Communication, values and society - Maslog, Crispin C. (Quezon City, Philippines : New Day Publishers, 1992)
This new book is intended as a textbook or main reference for another core course in the Philippine communication curricula, Communication and Society. This is in line with the goal of the Philippine Associatión of Communication Educators to produce indigenous instructional materials for our communication schools.
Communication and society -- Communication and values -- Communication, freedom and responsibility -- The Ethics of conflict reporting -- Press freedom and the law -- Press freedom and self-regulation in other countries.
Keywords: MASS MEDIA